2017
DOI: 10.20515/otd.300262
|View full text |Cite
|
Sign up to set email alerts
|

Özel Gereksinimi Olan Çocukların Ailelerinde Umutsuzluk ve Depresyon

Abstract: Bu çalışma, özel gereksinimi olan çocukların ailelerinde umutsuzluk düzeyinin saptanması, umutsuzluk ile ilgili olduğu düşünülen bazı değişkenlerin incelenmesi ve umutsuzluk ile depresyon arasındaki ilişkinin değerlendirilmesi amacı ile yapılmıştır. Çalışma, Sakarya ilindeki özel eğitim kurumlarında eğitim gören özel gereksinimi olan çocukların ebeveynleri üzerinde yapılmıştır. Çalışma süresince Sakarya ilindeki özel eğitim kurumlarına müracaat eden ve çalışmaya katılmayı kabul eden toplam 109 aile çalışma gru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 21 publications
2
8
1
1
Order By: Relevance
“…In the study, 64.6% of the sample group consisted of mothers. It was found that mothers were the most common caregivers in the studies which were conducted with the people who take care of their disabled children (Caicedo, 2014;Çatalbaş, Manav, & Ocakçı, 2015;Durat et al, 2017;Gürhopur & Dalgıç, 2017). Although the presence of a disabled child affects all family members, the primary caregiver mother is the most affected individual in this; process (Çalışır et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the study, 64.6% of the sample group consisted of mothers. It was found that mothers were the most common caregivers in the studies which were conducted with the people who take care of their disabled children (Caicedo, 2014;Çatalbaş, Manav, & Ocakçı, 2015;Durat et al, 2017;Gürhopur & Dalgıç, 2017). Although the presence of a disabled child affects all family members, the primary caregiver mother is the most affected individual in this; process (Çalışır et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As the degree of disability of the disabled child born with special needs increases, difficulties arise at different degrees for the family members. These difficulties are related with financial situation, lifestyle, education, psychological status, child's disability and social environment problems (Karadağ, 2009;Avşaroğlu & Gilik, 2017;Durat, Atmaca, Ünsal, & Kama, 2017). The child who is born with disability creates disappointment, confusion, guilt, helplessness, anxiety in the family (Burçak, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations